Churchill and Orwell [compact disc, unabridged] : the fight for freedom - Ricks, Thomas E. (Penguin Audio, 2017)
A dual portrait of Winston Churchill and George Orwell focuses on the pivotal years from the mid-1930s through the 1940s, describing how both suffered nearly fatal injuries before their vision and campaigns inspired action to preserve democracy throughoutthe world.